Small Residues Inhibit Homo-Dimerization of the Human Carbonic Anhydrase XII Transmembrane Domain - Florian Cymer (Membranes, 2021)
Amino acids with small side chains and motifs of small residues in a distance of four are rather abundant in human single-span transmembrane helices. While interaction of such helices appears to be common, the role of the small residues in mediating and/or stabilizing transmembrane helix oligomers remains mostly elusive. Yet, the mere existence of (small)xxx(small) motifs in transmembrane helices is frequently used to model dimeric TM helix structures. The single transmembrane helix of the human carbonic anhydrases XII contains a large number of amino acids with small side chains, and critical involvement of these small amino acids in dimerization of the transmembrane domain has been suggested. Using the GALLEX assay, we show here that the transmembrane domain indeed forms a strong transmembrane helix oligomer within a biological membrane. However, single or multiple mutations of small residue(s) to isoleucine almost always increased, rather than decreased, the interaction propensities. Reduction of helix flexibility and of protein–lipid contacts caused by a reduced lipid accessible surface area likely results in stabilization of helix–helix interactions within the membrane.